Foraminal height measurement techniques - Phan, Kevin; Mobbs, Ralph J.; Rao, Prashanth J. (Journal of Spine Surgery, 2015)
Background: One of the proposed advantages of anterior lumbar interbody fusion (ALIF) is restoration of disc height and hence an indirect foraminal height restoration. While this proposed advantage is often quoted in the literature, there are few robust studies demonstrating restoration of foraminal volume. Thus, this study aimed to review the literature and discuss the progression and development of foramen measurement techniques. Methods: A review of the literature was performed to identify studies which reported foraminal height and dimensions following fusion surgery in cadaveric models or patients. Results: Techniques in prior studies used to quantify foraminal dimensions before and after fusion operations include analysis from plain radiographs, computed tomography (CT) scans and magnetic resonance imaging (MRI) scans. Recent studies have attempted to standardize foraminal dimension measurements with the use of orthogonal software, accelerator-based measurements and the use of multiple images for three-dimensional reconstruction of the foramen volume. Conclusions: Consistent results have demonstrated significant increases in foraminal area and height following anterior lumbar interbody distraction, providing evidence that ALIF can indirectly increase foraminal height. Future studies should use standardized measurement approaches such as the Pedicle-to-Pedicle technique with CT or MRI images to determine changes in foraminal dimensions.